AL-QURâ€™AN DALAM PANDANGAN SYIâ€™AH - HM. Attamimy, HM (Jurnal THEOLOGIA, 2011)
However Sunni-Shia dichotomy is still felt in most Indonesian Muslims. In fact, not inferÂ¬quently, allegations that the Shiites are in the Islamic cult. However, the deveÂ¬lopment of Shi'ites in the country growing, triggered by the Islamic RevoÂ¬lution in Iran under Ayatollah Khumaini, has eroded little by little these baseÂ¬less accusations, so in some places, Muslims, whether Sunni sect embraced, or Shi'ites can live side by side in peace. Misunder-standing that occurred between the two mazhab were one by one can be explained so as can to reÂ¬move the mutual distrust between the two. One described here is the accusation that the Shiites have their own Qur'an different from Muslims in general. This accusation was unfounded because the Qur'an is used in the schools of Shi'a is exactly the same as those used by other Muslims. That they have Muá¹£á¸¥af â€˜AlÄ« and FÄá¹ima, it's true but the second position Muá¹£á¸¥af was nothing more than commentaries on the Qur'an is not the same as al-Quran. Kata Kunci: Syiâ€™ah, al-Qurâ€™Än, kesalahpahaman, Muá¹£á¸¥af â€˜AlÄ«, revolusi iran.